Resveratrol Induces Apoptosis and Attenuates Proliferation of MCF-7 Cells in Combination with Radiation and Hyperthermia - Amini, Peyman; Nodooshan, Saeedeh J.; Ashrafizadeh, Milad; Eftekhari, Seyed-Mohammad; Aryafar, Tayebeh; Khalafi, Leila; Musa, Ahmed Eleojo; Mahdavi, Seyed Rabie; Najafi, Masoud; Farhood, Bagher (Current Molecular Medicine, 2021)
Aim: In the current in vitro study, we tried to examine the possible role of resveratrol as a sensitizer in combination with radiotherapy or hyperthermia. Background: Breast cancer is the most common malignancy for women and one of the most common worldwide. It has been suggested that using non-invasive radiotherapy alone cannot eliminate cancer cells. Hyperthermia, which is an adjuvant modality, induces cancer cell death mainly through apoptosis and necrosis. However, cancer cells can also develop resistance to this modality. Objective: The objective of this study was to determine possible potentiation of apoptosis when MCF-7 cells treated with resveratrol before hyperthermia or radiotherapy. Methods: MCF-7 cancer cells were treated with different doses of resveratrol to achieve IC50%. Afterwards, cells treated with the achieved concentration of resveratrol were exposed to radiation or hyperthermia. Proliferation, apoptosis and the expression of pro-apoptotic genes were evaluated using flow cytometry, MTT assay and real-time PCR. Results for each combination therapy were compared to radiotherapy or hyperthermia without resveratrol. Results: Both irradiation or hyperthermia could reduce the viability of MCF-7 cells. Furthermore, the regulation of Bax and caspase genes increased, while Bcl-2 gene expression reduced. Resveratrol potentiated the effects of radiation and hyperthermia on MCF-7 cells. Conclusion: Results of this study suggest that resveratrol is able to induce the regulation of pro-apoptotic genes and attenuate the viability of MCF-7 cells. This may indicate the sensitizing effect of resveratrol in combination with both radiotherapy and hyperthermia.
Keywords: MCF-7